The Assessment: Economics of Transition in Eastern and Central Europe. - Allsopp, C; Kierzkowski, H (1997)
This Assessment provides an overview of the stylized facts and the underlying economic issues involved in transition, with a focus on the more successful reforming countries. Microeconomic, macroeconomic, and institutional factors interact. Particular emphasis is given to the initial output falls at the start of reform, where it is suggested that a generalized price-raising response by state enterprises to monetary tightness, liberalization, and devaluation was one of the main culprits. Trade liberalization has proved to be an extremely important and successful aspect of the strategies followed, but there are increasing dilemmas over exchange-rate policy at both the micro- and macroeconomic levels. A partial solution is further progress with institutional and, especially, banking-sector reform, but the policy conflicts will remain in an increasingly open and integrated international environment.